THE CURRENT STATE OF INDEPENDENT EDUCATION OF STUDENTS AND THE USE OF DIDACTIC MEANS IN ITS EFFECTIVE ORGANIZATION (Scientific journal of the Fergana State University, 2023)
This article focuses on the development of professional competence of students through the effective organization of independent learning in the higher education system. In the conducted scientific research, the state of organization of independent learning in the educational system was analyzed. Information on the organization of independent learning in the credit-module system was gathered by selecting separate subject and taking into account the distribution of hours allocated for the subject, as well as the use of modern didactic tools in the implementation of independent learning. Additionally, recommendations on using modern teaching platforms as a didactic tool in the organization of independent learning are given.